Pengaruh Kualitas Laporan Keuangan, Pemanfaatan Teknologi Informasi Dan Akuntabilitas Publik Terhadap Akuntabilitas Kinerja Direktorat Jenderal Penetapan Hak Dan Pendaftaran Tanah - Anggita, Destin; Kartikasari, Syarifah Ratih; Suharni, Siti (Fakultas Ekonomi - Universitas Setia Budi, 2023)
This study aims to examine the effect of the quality of financial reports, the use of information technology, and public accountability on the performance accountability of the Directorate General of Rights Determination and Land Registration. This type of research is a quantitative research. The population in this study amounted to 120 people and the sample amounted to 93 people. The technique in taking the sample using random sampling technique. Data collection techniques using questionnaires and documentation. The data analysis technique used multiple linear regression. The third variable can affect the accountability of the performance of the Directorate General of Determination of Rights and Land Registration by 48.3%.